Nanoestruturas de óxido de cobre obtidas por novo método hidrotermal de microondas - Almeida, Dawy Keyson de Araújo (Universidade Federal de São Carlos, 2006)
Synthesis and characterization of Copper Oxide nanostructured by means of hydrothermal assisted by microwaves were studied in this work. The thermal treatment device was set up by using a domestic microwave oven and a hydrothermal chamber, specially adapted as a hydrothermal reactor. The obtained nanostructures of CuO have been characterized by X-ray diffraction (XDR) to determine its crystallinity; by field emission scanning electron microscopy (SEM-FEG) and transmission electron microscopy to characterize the morphology and single crystal nature of nanocrystals formed. The mechanism of nanostructure formed and nanostructure morphology of CuO were studied us a function of processing conditions. For this, the influence of microwave processing, the nature of chemical basis and presence/absence of polyethylene glycol (PEG) as template have been considered during the formation of nanostructured CuO. The chemistry reaction for attaining the nanostructure of CuO was studied using stereochemistry concept and computational quantum chemistry. The results had demonstrated that the formation of copper oxide nanostructure depend on the stereochemistry of the template, on the chemical base for hydrothermal treatment and on the use of microwave heating for hydrothermal synthesis.
Keywords: Nanotecnologia; Nanoestruturas; Óxido de cobre; Hidrotermal de micro-ondas; CIENCIAS EXATAS E DA TERRA::QUIMICA